Clade 2.3.4.4b Highly Pathogenic Avian Influenza H5N1 Pathology in a Common Shorebird Species (Sanderling; Calidris alba) in Virginia, USA - Victoria A. Andreasen; Emily G. Phillips; Aidan M. O’Reilly; C. Robert Stilz; Rebecca L. Poulson; Ruth Boettcher; John K. Tracey; Nicole M. Nemeth (Animals)
Anseriformes (waterfowl) and Charadriiformes (shorebirds) are well-recognized natural reservoirs of low pathogenic (LP) influenza A viruses (IAVs). Historically, LP IAVs circulate among healthy individuals during seasonal, and often transcontinental, migrations. However, following the introduction of clade 2.3.4.4b highly pathogenic (HP) A/Goose/Guangdong/1/1996 lineage H5 IAV to North America in 2021, countless wild birds succumbed to fatal infections across the Western Hemisphere. Due to their small size and cryptic plumage patterns, opportunities for carcass recovery and postmortem evaluation in sanderlings (Calidris alba) and other shorebirds are rare. A multispecies mortality event in coastal Virginia, USA, in March–April 2024 included sanderlings among other wild bird species. Nine sanderlings underwent postmortem evaluation and clade 2.3.4.4b H5 IAV RNA was detected in pooled oropharyngeal-cloacal swabs from 11/11 individuals by real-time reverse transcription polymerase chain reaction. Histopathology was similar to that in waterfowl and included necrosis in the pancreas and brain and less commonly in the gonad, adrenal gland, spleen, liver, and intestine. Immunohistochemistry revealed IAV antigen labeling in necrotic neurons of the brain (neurotropism) and epithelial cells of the pancreas, gonad, and adrenal gland (epitheliotropism). Describing HP IAV-attributed pathology in shorebirds is key to understanding ecoepidemiology and population health threats in order to further document and compare pathogenesis among avian species.